2014
DOI: 10.1038/srep05089
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of Extracellular miRNAs in the Aqueous Humor of Glaucoma Patients Assessed with a Microarray System

Abstract: Aqueous humor (AH) is one of the body fluids in the eye, which is known to be related with various ocular diseases, but the complete RNAs characteristic of the AH in patients is not yet known. The aim of this study was, with a microarray analysis, to reveal the disease-related extracellular miRNAs profiles in individual patients AH. 100 μl of AH was collected by anterior chamber paracentesis from 10 glaucoma, 5 cataract, and 5 epiretinal membrane patients. The extracted total RNAs were shorter than 200 nt, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
94
5
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(101 citation statements)
references
References 45 publications
(58 reference statements)
0
94
5
2
Order By: Relevance
“…MicroRNAs play an important role in regulating the biological behavior of TM. [26][27][28] To determine the differential expression of miRNAs under oxidative stress, seven miRNAs, which may target the Smad family, were chosen, and the expression levels were detected by quantitative PCR (qPCR) (Fig. 2A).…”
Section: Mirnas Possibly Targeting Smad Family Are Downregulated In Hmentioning
confidence: 99%
“…MicroRNAs play an important role in regulating the biological behavior of TM. [26][27][28] To determine the differential expression of miRNAs under oxidative stress, seven miRNAs, which may target the Smad family, were chosen, and the expression levels were detected by quantitative PCR (qPCR) (Fig. 2A).…”
Section: Mirnas Possibly Targeting Smad Family Are Downregulated In Hmentioning
confidence: 99%
“…7 MicroRNAs are expressed in various ocular tissues with a distinct tissue-specific and developmental stage-specific expression pattern, which suggests potential unique functions. 8 They have also been detected in ocular fluids 9 and have been implicated in human corneal diseases like keratoconus, 10 Fuchs' dystrophy, 11 and herpetic stromal keratitis. 12 Corneal inflammation in fungal keratitis poses a significant therapeutic challenge to clinicians, particularly because of the controversial role of corticosteroids in the initial disease management.…”
mentioning
confidence: 99%
“…The increased level of miR-24 by TGF-β 1 is essential to contain the TGF-β 1 levels during cyclic mechanical stress which is brought about by the targeting of furin by miR-24. Yet another study identified many miRNAs in glaucoma with Hsa-let-7b-3p as the most prevalent in aqueous humor [83]. miRNA profiles not only reveal the specific pathophysiology, but also offer the diagnosis.…”
Section: Mirnas and Eye Disordersmentioning
confidence: 99%